Contribution of Multiwalled carbon nanotubes to dielectric and elastic properties in E7 nematic liquid crystal - Okutan, Mustafa; Yesilot, Gursel; Bolivar, Peter Haring (ELSEVIER, 2022)
In this article, electrical parameters, and elastic constants of nematic liquid crystal (NLC) contributed multiwalled carbon nanotubes (MCN) are presented by dielectric spectroscopy method. The effects of reorientation on the nematic liquid crystal by doping of multi-walled carbon nanotubes were investi-gated to reveal. Analyzes of dielectric strength Ae'(x), absorption coefficient a, relaxation time r, dielec-tric anisotropy Ae' (V), dielectric anisotropy ratio 7, splay elastic constant K11, and cross-over angular frequency wco of MCN contribution to E7 nematic liquid crystal with DC supply voltage are presented. Reorientation of elastic dipolar liquid crystal molecules was demonstrated by reducing the positive type (p type) dielectric anisotropy value in the broadband angular frequency range with the MCN contribution to the E7 coded nematic liquid crystal. The supply voltage applied to the NLC samples was observed to have nearly Debye-type relaxation mechanism in the host E7 LC structure, tending to switch to a Debye-type relaxation mechanism by MCN doping. Dipole effects were enhanced by doping of multi -walled carbon nanotubes in the orientation of elastic NLC molecules, and the relaxation time of host E7 NLC and doped MCN/E7 NLC decreased with increasing bias voltages. Cole-Cole analysis with different supply voltages, it has been seen that it turns into a new equivalent circuit depending on the MCN contribution.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: Liquid crystals; Multiwalled Carbon Nanotubes; Impedance Spectroscopy; Dielectric Anisotropy; Dielectric Strength; Splay Elastic Constant; Molecular Reorientation; CONSTANTS; LIGHT; DISPERSION; Chemistry; Physics